Distortion of the image of the partner with the syndrome of "emotional coldness" - Терещенко, Надія Миколаївна (Psychological Counseling and Psychotherapy)
The article on examples of counseling practices analyzed variants of the distortion of partner image corresponding to these options psychocorrectional strategy of the syndrome of "emotional coldness". Psychocorrectional strategy in cases of distortion of the image of the partner should be focused more on the structure of the syndrome of "emotional coldness" to ensure these distortions. Distortion may be associated with interpersonal dependency, and with contraddiction and with the fear of psychological intimacy and other phenomena. The most characteristic distortion of the image of a partner in the syndrome of "emotional coldness" is the loss of the real, dynamic personality traits partner, which complicates the possibility of constructing satisfactory, stable relations of psychological intimacy.